The role of Malcolm Clarke (1930–2013) in the Azores as a scientist and educationist. (8th July 2014) - Gomes-Pereira, J.N.; Prieto, R.; Neves, V.; Xavier, J.; Pham, C.; Gonçalves, J.; Porteiro, F.; Santos, R.; Martins, H.
Abstract : Malcolm Roy Clarke (1930–2013) was a British teuthologist who made an important contribution to marine science in the Azores archipelago (Portugal). Malcolm started doing research in the Azores from 1980s onward, settling for residency in 2000 after retirement (in 1987). He kept publishing on Azorean cephalopods collaborating in 20% of the peer reviewed works focusing on two main areas: dietary studies; and the ecology of cephalopods on seamounts. Since his first visit in 1981, he was involved in the description of the dietary ecology of several cetaceans, seabirds, and large pelagic and deep-water fish. Using his own data, Malcolm revised the association of cephalopods with seamounts, updating and enlarging the different cephalopod groups according to species behaviour and ecology. Malcolm taught several students working in the Azores on cephalopods and beak identification, lecturing the Third International Workshop in Faial (2007). He empowered the recently established research community, by providing important contacts with foreign institutes and informal advice. He collaborated in the regional cetacean stranding network (RACA) and was an active member of the advisory board of the journal Arquipelago—Life and Marine Sciences . But the scientific role of Malcolm Clarke in the Azores went beyond his academic activities. In the last 10 years Malcolm and Dot Clarke dedicated themselves to building and running a museum on Pico Island, showing the biology of the sperm whale and its interaction with squid; a cultural and touristic legacy for future generations to enjoy.